REVITALISASI PERAN PEMBELAJARAN IPS DALAM PEMBENTUKAN KARAKTER BANGSA - Sardiman Sardiman (Jurnal Cakrawala Pendidikan, 2010)
Abstract: Revitalization of Roles of the Learning of Social Studies in the NationsCharacter Building. Revitalization of roles of the learning of social studies needs tobe made as soon as possible, because so far the learning implementation is notrelevant to its objective and purpose. The learning of social studies has animportant role in character education. Therefore, it is necessary to makeimprovement and upgrade steps. The curriculum design and competence standardof graduates should be based on student reality and humanity values, and shouldemphasize not only on materials mastery. The approach of essentialism has to bechanged into the social reconstruction theory. The learning process is developed asa cultural transaction process which becomes an inseparable part of studentcharacter development. The learning model emphasizes more on active andparticipative learning. Besides, in order to strenghten roles of the learning of socialstudies in developing character education, a good environment condition,including the political will from the government, is needed.Keywords: revitalization, character education, learning of social studies